ANALISIS TINGKAT KESEHATAN BANK PERKREDITAN RAKYAT (BPR) KAITANNYA TERHADAP PEROLEHAN LABA (Studi Kasus Pada PT BPR Shinta Daya Kalasan Di Yogyakarta) - Husein Pulungan, Muhammad Sadat (Jurnal Manajemen dan Keuangan, 2009)
He assessment of the level of the health of the bank in this case was the Perkreditan Rakyat Bank that used the CAMEL method, by means of measuring the component from respectively the factor that is the Capitalisation factor, Kualitas of the Asset, Manajemen, Rentabilitas and the Liquidity. This analysis method was the Banks Indonesian output as being applied in the Banks Indonesian Circular No.30/3/UPPB and the Instruction on the Management of the Indonesian Bank, The date 30 30April 1997 and still current now. This research was the case study to BPR Shinta Daya Kalasan Periode in 2003 up to 2005 with the aim of the research of being to receive the picture that was sharp about the measurement of the level of the health of the BPR Shinta Daya Kalasan bank.The analysis of the data was during 2004 received by results of the Capital assessment with Capital Adequacy Ratio 15.69 %, thought factor credit 100, Quality assets with the ratio of the quality of the productive asset 2.49 %, thought factor credit 100, and the Penyisigan Peghapusan Aktiva Produktif ratio 94.32 %, thought factor credit 94.32, the management with the value of the public of management credit 13,33dan the management of the risk 19, Earning with the ratio Return ounce Asset 5.28 %, thought factor credit 100, and the cost oprasional towards the income operational 87.63 %, thought factor credit 100, Liquidity with Cash Ratio 7.19 %, thought factor credit 100, and Loan to Deposit Ratio 95.05 %, thought factor credit 79.80.Keywords : Acquisition Profit